PENGARUH KUALITAS TEKNOLOGI INFORMASI, KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWANPADA PT. PLN BATAM - tukino tukino (Universitas Putera Batam, 2013)
PLN Batam is a services company in batam. The purpose of this study was to determine effects of Quality Information Technology for Employee Performance. To determine the use of Information Technology and Work Motivation on Employee Performance. Research object PT. PLN Batam with the unit of analysis Employees PT. PLN Batam. The data was obtained using a questionnaire and interviewed staff and leadership PT. PLN Batam. Use of Information Technology and Work Motivation affect employee performance simultaneously at PT. PLN Batam. In the implementation, PT. PLN Batam is less attention to the balance of the services offered by PT. PLN Batam to its employees so that the use of Information Technology PT. PLN Batam for Employee Performance influential but less than optimal. Quality Information Technology provides information that is useful for customers by enabling customer service, employee competence is currently perceived by the customers PT. PLN Batam, work motivation is perceived as better by customers PT. PLN Batam. Although not all of the customer acknowledge the good work motivation, but based on the results of this study concluded that the majority of customers found that perceived work motivation is quite good, Employee Performance individuals and groups perceived to have provided enough benefit to customer service, quality of Information Technology In partial influence positive and significant impact on employee performance, partially Competence, providing a positive and significant impact on Employee Performance, Motivation partially Working, providing a positive and significant impact on Employee Performance and Quality simultaneously information Technology, Occupational Competence and Motivation significant positive influence on Employee performance.